Artificial limbs, etc. for Spanish refugees : memorandum of interview, with Walter Schevenels - Jeger, George ; Schevenels, Walther, b. 1894; Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1940-01-29 C02-0027-001 292C/946/2/27(i)